IoT in Arctic Tourism – A Case-study of the Tourist Information Office in Narvik - Mustafa, Ayah Mohamad Yazid Faisal; Noureddine, Rami; Thordarson, Diana Santalova (FRUCT, 2022)
Source at: https://fruct.org/publications/volume-32/acm32/